A kind of amino and amidoxime group synergistically modified SiO 2 Preparation method and application of loofah composite material

By epoxy modification of SiO2 and loofah, combined with polyamine compounds for composite and crosslinking, the synergistic modification of the SiO2/loofah composite material was prepared through cyanolysis and amidoxime reaction, which solved the problems of difficult recycling, poor structural stability and poor adsorption effect of existing materials, and achieved efficient and stable uranium adsorption and easy recovery.

CN119746823BActive Publication Date: 2025-05-02CHANGSHU INSTITUTE OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510273153.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-05-02
Estimated Expiration
2045-03-10

AI Technical Summary

Technical Problem

Existing nanopowder materials and fiber materials have difficulty in recycling, poor structural stability, weak adsorption effect and potential threats to the marine environment in the adsorption and separation of uranium in seawater.

Method used

SiO2 and loofah are modified by epoxy silane, combined with polyamine compounds for composite and crosslinking, and further prepared a synergistically modified SiO2/loofah composite material with amino group and geminoxime group.

Benefits of technology

The structural stability of the composite material and the adsorption capacity of uranyl ions are significantly improved, the selectivity to uranium is enhanced, and the material is easy to recover.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a SiO2 / loofah composite material synergistically modified by amino and amidoxime groups, comprising the steps of: modifying alkali pre-treated loofah and SiO2 nanoparticles respectively by epoxy silane to obtain epoxylated loofah and epoxylated SiO2 nanoparticles; ultrasonically dispersing the two in a solvent, performing composite cross-linking modification with a polyamine compound as a cross-linking agent to obtain an amino SiO2 / loofah composite material; then adding cyanoacetic acid and a catalyst to a solution containing the composite material for stirring reaction to obtain a cyanated SiO2 / loofah composite material with surface modified cyano groups; and then performing an amidoxime reaction to obtain an amino and amidoxime-synergistically modified SiO2 / loofah composite material. The invention improves the structural stability of the loofah matrix and exerts the synergistic adsorption effect of SiO2 nanomaterials, loofah, amidoxime groups and amino groups on uranium.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid adsorbents, and in particular to a preparation method and application of a SiO2 / loofah composite material synergistically modified by amino and amidoxime groups. Background Art

[0002] The research on adsorption and separation of uranium in seawater mainly focuses on two major areas: nanopowder materials and fiber materials.

[0003] Nanopowder materials have excellent adsorption capacity and good selectivity for uranium. However, these powder materials are not easy to recycle and face many challenges in actual use, such as agglomeration and leakage. These problems not only weaken their adsorption effect, but also pose a potential threat to the marine environment.

[0004] In addition, fiber adsorption materials, especially amidoxime-functionalized fibers, have attracted much attention due to their unique chelating ability for uranium. As a natural fiber material, loofah not only has a series of advantages such as excellent hydrophilicity, low cost and developed pore structure, but also the rich functional groups on the surface make it easier to functionalize, thus becoming an ideal carrier for amidoxime groups. However, loofah modified with a single amidoxime group is more effective in improving uranium adsorption performance. Moreover, in practical applications, adsorption materials must withstand the test of various external forces such as physical extrusion and friction, and also cope with complex and changeable environmental conditions such as pH changes and temperature fluctuations. The structural stability of loofah is difficult to cope with these challenges, and its structure is prone to deformation or even damage during use, which directly affects the adsorption capacity and service life of amidoxime-modified loofah. Summary of the invention

[0005] In view of the above-mentioned defects of the prior art, the present invention provides a method for preparing an amino and amidoxime-synergistically modified SiO2 / loofah composite material, which improves the adsorption effect of the loofah composite material on uranium and the structural stability, improves the adsorption capacity and durability of the composite material, and ensures its easy recovery.

[0006] The technical scheme of the present invention is as follows: A method for preparing a SiO2 / loofah composite material synergistically modified by amino and amidoxime groups, comprising the following steps:

[0007] (1) Alkaline solution pretreated loofah sponge and SiO2 nanoparticles were modified by epoxy silane to obtain epoxylated loofah sponge and epoxylated SiO2 nanoparticles;

[0008] (2) After the epoxylated loofah and epoxylated SiO2 nanoparticles are ultrasonically dispersed in a solvent, a polyamine compound is used as a crosslinking agent to carry out composite and crosslinking modification between the epoxylated loofah and the epoxylated SiO2 nanoparticles to obtain an amino SiO2 / loofah composite material;

[0009] (3) adding cyanoacetic acid and a catalyst to a solution containing the aminated SiO2 / loofah composite material and stirring the solution to react, thereby modifying the surface of the aminated SiO2 / loofah composite material with cyano groups to obtain a cyanated SiO2 / loofah composite material;

[0010] (4) subjecting the cyanated SiO2 / loofah composite material to an amidoximation reaction to obtain an amino- and amidoxime-synergistically modified SiO2 / loofah composite material.

[0011] Furthermore, the step (1) specifically comprises adding the alkali solution pretreated loofah into toluene for ultrasonic dispersion, then adding epoxy silane for reaction, and adding SiO2 nanoparticles into toluene for ultrasonic dispersion, then adding epoxy silane for reaction, and filtering, washing and drying after the reaction to obtain epoxylated loofah and epoxylated SiO2, wherein the mass ratio of the alkali solution pretreated loofah to epoxy silane is 1: (0.5-2), and the mass ratio of the SiO2 nanoparticles to epoxy silane is 1: (0.5-2). The epoxy silane is preferably γ-glycidyloxypropyltrimethoxysilane.

[0012] Furthermore, the reaction temperature in step (1) is 80-100° C., and the reaction time is 8-12 h.

[0013] Furthermore, the step (2) specifically comprises adding epoxylated loofah and epoxylated SiO2 nanoparticles into 1,4-dioxane, uniformly dispersing by ultrasonication, and then adding a polyamine compound to react, filtering, washing, and drying after the reaction to obtain an amino SiO2 / loofah composite material, wherein the mass ratio of the epoxylated loofah, the epoxylated SiO2 nanoparticles, and the polyamine compound is 1: (0.5-1): (0.4-0.8).

[0014] Furthermore, the polyamine compound is one of triethylenetetramine, tetraethylenepentamine and pentaethylenehexamine, and the reaction in step (2) is carried out under nitrogen protection, the reaction temperature is 70-90° C., and the reaction time is 4-6 hours.

[0015] Furthermore, the step (3) specifically comprises adding the aminated SiO2 / loofah composite material into dichloromethane, then adding cyanoacetic acid and a catalyst to carry out stirring reaction, filtering after the reaction, repeatedly washing with deionized water, and drying to obtain the cyanated SiO2 / loofah composite material, wherein the mass ratio of the aminated SiO2 / loofah composite material, cyanoacetic acid and catalyst is 1: (0.5-1.5): (0.2-0.6).

[0016] Furthermore, the catalyst is benzenesulfonic acid, the stirring reaction temperature in step (3) is 60-80° C., and the reaction time is 5-8 h.

[0017] Furthermore, the step (4) specifically comprises preparing an aqueous solution of hydroxylamine or an aqueous solution of hydroxylamine salt and adjusting the pH to 7-8, then adding the prepared cyanated SiO2 / loofah composite material to carry out an oxime reaction, and after the reaction, filtering, washing and drying to obtain an amino and amidoxime-synergistically modified SiO2 / loofah composite material.

[0018] Furthermore, the concentration of the aqueous solution of hydroxylamine and the aqueous solution of hydroxylamine salt is 8% to 10%, the temperature of the amine oximation reaction in step (4) is 60 to 80° C., and the reaction time is 12 to 16 hours.

[0019] Another technical solution of the present invention is the application of an amino and amidoxime synergistically modified SiO2 / loofah composite material, wherein the amino and amidoxime synergistically modified SiO2 / loofah composite material obtained by the preparation method of the amino and amidoxime synergistically modified SiO2 / loofah composite material is used to adsorb uranium ions in water.

[0020] The present invention firstly uses epoxysilane to carry out epoxy modification on SiO2 and loofah, then uses polyamine as a bridging structure, utilizes the ring-opening reaction of epoxy group and amino group, effectively realizes the compound and cross-linking between SiO2 and loofah, which not only significantly enhances the structural stability of SiO2 / loofah composite material, but also adds abundant amino functional groups inside the material, and these amino groups can further enhance the affinity of the subsequently introduced amidoxime group to uranyl ion. Finally, the present invention utilizes a large number of hydroxyl groups generated by the ring-opening reaction as anchor points, and through esterification reaction, modifies a large number of cyano groups on the inner and outer surfaces of the SiO2 / loofah composite material, and further performs amidoxime treatment on these cyano groups, thereby preparing a SiO2 / loofah composite material having both the dual modification effects of amino group and amidoxime group and having a cross-linked structure.

[0021] The advantages of the present invention compared with the prior art are:

[0022] (1) The present invention cross-links SiO2 nanoparticles and compounds them into an easily recyclable loofah matrix, thereby overcoming the problem that nanopowder materials are difficult to recycle as adsorbents.

[0023] (2) The present invention simultaneously performs dual modification of compounding and cross-linking on the loofah sponge, which significantly enhances the overall structural stability of the material, allowing it to maintain a longer service life and better performance during use.

[0024] (3) The composite material prepared by the present invention can give full play to the synergistic adsorption effect of amino group, amidoxime group, SiO2 and loofah sponge, greatly improving its adsorption capacity for uranyl ions. In addition, the amidoxime group and amino group rich in the composite material further improve its selectivity for uranyl ions. DETAILED DESCRIPTION

[0025] The present invention will be further described below in conjunction with the embodiments, but are not intended to limit the present invention.

[0026] Example 1

[0027] A method for preparing a SiO2 / loofah composite material synergistically modified by amino and amidoxime groups comprises the following steps:

[0028] (1) Epoxy

[0029] After peeling and removing the seeds from the ripe loofah fruit, immerse it in distilled water and squeeze it several times until no impurities fall off and the color changes. Then immerse the loofah in new distilled water again, change the water every 3 hours, take it out after 15 hours, dry it naturally and cut it into 0.3 cm samples. Soak the sample in a 10% NaOH aqueous solution, stir it at 80°C for 3 hours, take it out and wash it with distilled water until it is neutral, and dry it for use. The concentration of the NaOH aqueous solution in the alkali solution pretreatment step can be 2% to 15%, and the conditions for the immersion and stirring treatment can be stirring at 60 to 100°C for 2 to 5 hours.

[0030] 1g of loofah pretreated with alkali solution was added to toluene, ultrasonically dispersed evenly, 0.5g of γ-glycidyloxypropyltrimethoxysilane was added, stirred and reacted at 80°C for 12h, and then filtered, washed repeatedly with deionized water, and dried to obtain epoxylated loofah. 1g of SiO2 nanoparticles was added to toluene, ultrasonically dispersed evenly, 0.5g of γ-glycidyloxypropyltrimethoxysilane was added, stirred and reacted at 80°C for 12h, and then filtered, washed repeatedly with deionized water, and dried to obtain epoxylated SiO2.

[0031] (2) Cross-linking and composite modification while introducing a large number of amino groups

[0032] 1 g of epoxylated loofah and 0.5 g of epoxylated SiO2 nanoparticles were added to 1,4-dioxane and evenly dispersed by ultrasonication. Then, 0.4 g of triethylenetetramine was added and the reaction solution was reacted at 70°C under nitrogen protection for 6 h. After the reaction, the solution was filtered, repeatedly washed with deionized water and dried to obtain an amino-rich amino-containing SiO2 / loofah composite material.

[0033] (3) Cyanation

[0034] 1 g of the prepared amination SiO2 / loofah composite material was immersed in dichloromethane, and then 0.5 g of cyanoacetic acid and 0.2 g of benzenesulfonic acid (catalyst) were added. The reaction solution was stirred at 60°C for 8 h. After the reaction, it was filtered, repeatedly washed with deionized water, and dried to obtain a cyanation SiO2 / loofah composite material rich in amino and cyano groups.

[0035] (4) Amine oximation reaction

[0036] Prepare an aqueous solution of hydroxylamine hydrochloride with a concentration of 8%, add NaOH to adjust the solution pH to 7, then add the above-prepared cyanated SiO2 / loofah composite material rich in amino and cyano groups, stir the reaction solution at 60°C for 16 hours, filter after the reaction, wash with deionized water, and dry to obtain the amino and amidoxime synergistically modified SiO2 / loofah composite material.

[0037] The adsorption capacity test experiment of the amino and amidoxime group-modified SiO2 / loofah composite material for uranyl ions prepared in Example 1 is as follows:

[0038] Prepare 100 mL of uranyl aqueous solution (uranyl nitrate as solute) with a concentration of 100 mg / L in a flask, adjust the solution pH to 7 with 0.1 M NaOH, add the prepared amino and amidoxime synergistically modified SiO2 / loofah composite material, and then adsorb for 6 hours at 200 rpm in a constant temperature oscillator at 25°C. After adsorption, take the upper clear liquid, and use ICP-AES to determine the concentration of remaining uranyl ions in the clear liquid. The adsorption amount of uranyl ions by the adsorbent material is calculated by the following formula ( Q , mg / g), and the results are listed in Table 1.

[0039] Q =( C 0 - C t ) V / M

[0040] Q is the adsorption capacity (mg / g); C 0 is the initial concentration of uranyl ions (mg / L); Ct is the concentration of uranyl ions after adsorption (mg / L); V is the volume of the solution (L); M is the mass of the adsorbent (mg).

[0041] Example 2

[0042] A method for preparing a SiO2 / loofah composite material synergistically modified by amino and amidoxime groups comprises the following steps:

[0043] (1) Epoxy

[0044] The loofah was treated with alkali solution in the same manner as in Example 1. 1 g of loofah pretreated with alkali solution was added to toluene, ultrasonically dispersed evenly, 1 g of γ-glycidyloxypropyltrimethoxysilane was added, stirred and reacted at 90°C for 10 h, and filtered after reaction, repeatedly washed with deionized water, and dried to obtain epoxylated loofah. 1 g of SiO2 nanoparticles was added to toluene, ultrasonically dispersed evenly, 1 g of γ-glycidyloxypropyltrimethoxysilane was added, stirred and reacted at 90°C for 10 h, and filtered after reaction, repeatedly washed with deionized water, and dried to obtain epoxylated SiO2.

[0045] (2) Cross-linking and composite modification while introducing a large number of amino groups

[0046] 1 g of epoxylated loofah and 0.75 g of epoxylated SiO2 nanoparticles were added to 1,4-dioxane and evenly dispersed by ultrasonic. Then, 0.6 g of tetraethylenepentamine was added and the reaction solution was reacted at 80°C under nitrogen protection for 5 h. After the reaction, the solution was filtered, repeatedly washed with deionized water and dried to obtain an amino-rich amino-containing SiO2 / loofah composite material.

[0047] (3) Cyanation

[0048] 1 g of the prepared amination SiO2 / loofah composite material was immersed in dichloromethane, and then 1 g of cyanoacetic acid and 0.4 g of benzenesulfonic acid (catalyst) were added, and the reaction solution was stirred at 70°C for 6.5 h. After the reaction, it was filtered, repeatedly washed with deionized water, and dried to obtain a cyanation SiO2 / loofah composite material rich in amino and cyano groups.

[0049] (4) Amine oximation reaction

[0050] A 9% aqueous solution of hydroxylamine hydrochloride was prepared, NaOH was added to adjust the pH of the solution to 7.5, and then the cyanated SiO2 / loofah composite material rich in amino and cyano groups prepared above was added, the reaction solution was stirred and reacted at 70°C for 14 hours, and after the reaction, it was filtered and washed with deionized water. After drying, the amino and amidoxime group synergistically modified SiO2 / loofah composite material was obtained, and its adsorption capacity for uranyl ions was measured according to the adsorption performance experiment of the product in Example 1, and the results are listed in Table 1.

[0051] Example 3

[0052] A method for preparing a SiO2 / loofah composite material synergistically modified by amino and amidoxime groups comprises the following steps:

[0053] (1) Epoxy

[0054] The loofah was treated with alkali solution in the same manner as in Example 1. 1 g of loofah pretreated with alkali solution was added to toluene, ultrasonically dispersed uniformly, 2 g of γ-glycidyloxypropyltrimethoxysilane was added, stirred and reacted at 100°C for 8 h, and filtered after reaction, repeatedly washed with deionized water, and dried to obtain epoxylated loofah. 1 g of SiO2 nanoparticles was added to toluene, ultrasonically dispersed uniformly, 2 g of γ-glycidyloxypropyltrimethoxysilane was added, stirred and reacted at 100°C for 8 h, and filtered after reaction, repeatedly washed with deionized water, and dried to obtain epoxylated SiO2.

[0055] (2) Cross-linking and composite modification while introducing a large number of amino groups

[0056] 1 g of epoxylated loofah and 1 g of epoxylated SiO2 nanoparticles were added to 1,4-dioxane and evenly dispersed by ultrasonic. Then, 0.8 g of pentaethylenehexamine was added and the reaction solution was reacted at 90°C under nitrogen protection for 4 h. After the reaction, the solution was filtered, repeatedly washed with deionized water and dried to obtain an amino-rich amino-containing SiO2 / loofah composite material.

[0057] (3) Cyanation

[0058] 1 g of the prepared amination SiO2 / loofah composite material was immersed in dichloromethane, and then 1.5 g of cyanoacetic acid and 0.6 g of benzenesulfonic acid (catalyst) were added, and the reaction solution was stirred at 80°C for 5 hours. After the reaction, it was filtered, repeatedly washed with deionized water, and dried to obtain a cyanation SiO2 / loofah composite material rich in amino and cyano groups.

[0059] (4) Amine oximation reaction

[0060] Prepare a 10% aqueous solution of hydroxylamine hydrochloride, add NaOH to adjust the solution pH to 8, then add the above-prepared cyanated SiO2 / loofah composite material rich in amino and cyano groups, and heat the reaction solution at 80 o C and stirred for 12 h. After the reaction, the mixture was filtered and washed with deionized water. After drying, the amino and amidoxime synergistically modified SiO2 / loofah composite material was obtained. The adsorption capacity of the composite material for uranyl ions was determined according to the adsorption performance experiment of the product in Example 1. The results are listed in Table 1.

[0061] Comparative Example 1

[0062] A method for preparing amidoxime-modified loofah comprises the following steps:

[0063] The loofah was treated with alkali solution in the same manner as in Example 1. 1 g of the loofah pretreated with alkali solution was added to dichloromethane, and then 0.5 g of cyanoacetic acid and 0.2 g of benzenesulfonic acid (catalyst) were added, and the reaction solution was stirred at 60°C for 8 hours. After the reaction, the loofah was filtered, repeatedly washed with deionized water, and dried to obtain amidoxime-modified loofah. The adsorption capacity of the loofah for uranyl ions was measured according to the adsorption performance experiment of the product in Example 1, and the results are listed in Table 1.

[0064] Comparative Example 2

[0065] A method for preparing amino-amidoxime-synergistically modified loofah comprises the following steps:

[0066] (1) Epoxy

[0067] The loofah was treated with alkali solution in the same manner as in Example 1. 1 g of loofah pretreated with alkali solution was added to toluene, ultrasonically dispersed uniformly, 0.5 g of γ-glycidyloxypropyltrimethoxysilane was added, stirred and reacted at 80° C. for 12 h, and after the reaction, suction filtration, deionized water repeated washing, and drying were performed to obtain epoxylated loofah.

[0068] (2) Cross-linking modification and simultaneous introduction of amino groups

[0069] 1 g of epoxylated loofah was added to 1,4-dioxane and evenly dispersed by ultrasonication. Then, 0.4 g of triethylenetetramine was added and the reaction solution was reacted at 70°C for 6 h under nitrogen protection. After the reaction, the loofah was filtered, repeatedly washed with deionized water and dried to obtain amino-rich loofah.

[0070] (3) Cyanation

[0071] 1 g of the prepared amino-rich loofah was added to dichloromethane, and then 0.5 g of cyanoacetic acid and 0.2 g of benzenesulfonic acid (catalyst) were added. The reaction solution was stirred at 60°C for 8 hours. After the reaction, it was filtered, repeatedly washed with deionized water, and dried to obtain amino- and cyano-rich loofah.

[0072] (4) Amine oximation reaction

[0073] An aqueous solution of hydroxylamine hydrochloride with a concentration of 8% was prepared, NaOH was added to adjust the solution pH to 7, and then the cyanated loofah prepared above was added, and the reaction solution was stirred at 60° C. for 16 hours. After the reaction, it was filtered and washed with deionized water. After drying, the amino and amidoxime synergistically modified loofah was obtained, and its adsorption capacity for uranyl ions was measured according to the adsorption performance experiment of the product in Example 1, and the results are listed in Table 1.

[0074] Comparative Example 3

[0075] A method for preparing an amino-modified SiO2 / loofah composite material comprises the following steps:

[0076] (1) Epoxy

[0077] The loofah was treated with alkali solution in the same manner as in Example 1. 1 g of loofah pretreated with alkali solution was added to toluene, ultrasonically dispersed evenly, 0.5 g of γ-glycidyloxypropyltrimethoxysilane was added, stirred and reacted at 80°C for 12 h, and filtered after reaction, washed repeatedly with deionized water, and dried to obtain epoxylated loofah. 1 g of SiO2 nanoparticles was added to toluene, ultrasonically dispersed evenly, 0.5 g of γ-glycidyloxypropyltrimethoxysilane was added, stirred and reacted at 80°C for 12 h, and filtered after reaction, washed repeatedly with deionized water, and dried to obtain epoxylated SiO2.

[0078] (2) Cross-linking and composite modification while introducing a large number of amino groups

[0079] 1 g of epoxylated loofah and 0.5 g of epoxylated SiO2 nanoparticles were added to 1,4-dioxane and evenly dispersed by ultrasonic. Then, 0.4 g of triethylenetetramine was added. The reaction solution was reacted at 70°C under nitrogen protection for 6 h. After the reaction, the mixture was filtered, repeatedly washed with deionized water, and dried to obtain an amino-modified SiO2 / loofah composite material. The adsorption capacity of the composite material for uranyl ions was measured according to the adsorption performance experiment of the product in Example 1. The results are listed in Table 1.

[0080] Table 1 Adsorption capacity of uranyl ions of the adsorbent materials prepared in Examples 1-3 and Comparative Examples 1-3

[0081]

[0082] It can be seen from the above results that in the embodiments of the present invention, the SiO2 / loofah composite material with good hydrophilicity and developed pore structure is used as a carrier, the amidoxime group with strong affinity for uranyl ions is used as an adsorption group, and the amino group that can improve the binding force of the amidoxime group to the uranyl ion is used as a synergistic adsorption group. Therefore, the prepared adsorption material can fully synergistically exert the adsorption effect of loofah, SiO2, amidoxime group and amino group on uranyl ions, so that it shows excellent ability in uranium extraction, and the adsorption amount of uranyl ions can reach 529 mg / g.

[0083] In contrast, in Comparative Example 1, only amidoxime groups were introduced into the loofah, lacking the synergistic effect of amino groups and SiO2; Comparative Example 2 simultaneously introduced amidoxime groups and amino groups into the loofah, but ignored the importance of SiO2 composite modification. In Comparative Example 3, the loofah was composited and modified with multiple amino groups, but the amidoxime groups with strong affinity for uranyl ions were not modified. Therefore, the modified loofah materials obtained in these three comparative examples could not be compared with the SiO2 / loofah composite materials obtained in the examples in terms of the number of adsorption groups and the richness of the pore structure, resulting in a significant reduction in their adsorption capacity for uranyl ions.

Claims

1. A method for preparing a SiO2 / loofah composite material synergistically modified by amino and amidoxime groups, characterized in that: The following steps are involved: (1) Alkaline solution pretreated loofah sponge and SiO2 nanoparticles were modified by epoxy silane to obtain epoxylated loofah sponge and epoxylated SiO2 nanoparticles; (2) After the epoxylated loofah and epoxylated SiO2 nanoparticles are ultrasonically dispersed in a solvent, a polyamine compound is used as a crosslinking agent to carry out composite and crosslinking modification between the epoxylated loofah and the epoxylated SiO2 nanoparticles to obtain an amino SiO2 / loofah composite material; (3) adding cyanoacetic acid and a catalyst to a solution containing the aminated SiO2 / loofah composite material and stirring the solution to react, thereby modifying the surface of the aminated SiO2 / loofah composite material with cyano groups to obtain a cyanated SiO2 / loofah composite material; (4) subjecting the cyanated SiO2 / loofah composite material to an amidoximation reaction to obtain an amino- and amidoxime-based synergistically modified SiO2 / loofah composite material.

2. The method for preparing the amino-amidoxime-synergistically modified SiO2 / loofah composite material according to claim 1, characterized in that: The step (1) specifically comprises adding the alkali solution pretreated loofah into toluene for uniform ultrasonic dispersion, then adding epoxy silane for reaction, and adding SiO2 nanoparticles into toluene for uniform ultrasonic dispersion, then adding epoxy silane for reaction, and after the reaction, filtering, washing and drying are respectively performed to obtain epoxylated loofah and epoxylated SiO2, wherein the mass ratio of the alkali solution pretreated loofah to epoxy silane is 1:(0.5-2), and the mass ratio of the SiO2 nanoparticles to epoxy silane is 1:(0.5-2).

3. The method for preparing the synergistic modified SiO2 / loofah composite material of amino and amidoxime groups according to claim 2, characterized in that: The reaction temperature in step (1) is 80-100° C., and the reaction time is 8-12 hours.

4. The method for preparing the SiO2 / loofah composite material synergistically modified by amino and amidoxime groups according to claim 1, characterized in that: The step (2) specifically comprises adding epoxylated loofah and epoxylated SiO2 nanoparticles into 1,4-dioxane, uniformly dispersing them by ultrasonication, and then adding a polyamine compound to react. After the reaction, the composite material of amino SiO2 / loofah is obtained by filtering, washing and drying. The mass ratio of the epoxylated loofah, the epoxylated SiO2 nanoparticles and the polyamine compound is 1: (0.5-1): (0.4-0.8).

5. The method for preparing the amino-amidoxime-synergistically modified SiO2 / loofah composite material according to claim 4, characterized in that: The polyamine compound is one of triethylenetetramine, tetraethylenepentamine and pentaethylenehexamine. The reaction in step (2) is carried out under nitrogen protection, the reaction temperature is 70-90° C., and the reaction time is 4-6 hours.

6. The method for preparing the amino-amidoxime-synergistically modified SiO2 / loofah composite material according to claim 1, characterized in that: The step (3) specifically comprises adding the aminated SiO2 / loofah composite material into dichloromethane, then adding cyanoacetic acid and a catalyst to carry out stirring reaction, filtering after the reaction, repeatedly washing with deionized water, and drying to obtain the cyanated SiO2 / loofah composite material, wherein the mass ratio of the aminated SiO2 / loofah composite material, cyanoacetic acid and catalyst is 1: (0.5-1.5): (0.2-0.6).

7. The method for preparing the amino-amidoxime-synergistically modified SiO2 / loofah composite material according to claim 6, characterized in that: The catalyst is benzenesulfonic acid, the stirring reaction temperature in step (3) is 60-80° C., and the reaction time is 5-8 hours.

8. The method for preparing the amino-amidoxime-synergistically modified SiO2 / loofah composite material according to claim 1, characterized in that: The step (4) specifically comprises preparing an aqueous solution of hydroxylamine or an aqueous solution of hydroxylamine salt and adjusting the pH to 7-8, then adding the prepared cyanated SiO2 / loofah composite material to carry out an oxime reaction, and after the reaction, filtering, washing and drying to obtain an amino and amidoxime-synergistically modified SiO2 / loofah composite material.

9. The method for preparing the amino-amidoxime-synergistically modified SiO2 / loofah composite material according to claim 8, characterized in that: The concentration of the aqueous solution of hydroxylamine and the aqueous solution of hydroxylamine salt is 8% to 10%, the temperature of the amine oximation reaction in step (4) is 60 to 80° C., and the reaction time is 12 to 16 hours.

10. An application of an amino group and amidoxime group synergistically modified SiO2 / loofah composite material, characterized in that: The SiO2 / loofah composite material synergistically modified by amino and amidoxime groups obtained by the preparation method of the SiO2 / loofah composite material synergistically modified by amino and amidoxime groups as described in any one of claims 1 to 9 is used to adsorb uranium ions in water.

Citation Information

Patent Citations

  • Amino-amidoximino bifunctional super-crosslinked microporous uranium adsorbent and preparation method thereof

    CN111804285A

  • Chemical modification method for improving heavy metal adsorption performance of loofah sponge

    CN119140075A